Fisheries Management of Terubuk (Tenualosa macrura) with an Ecosystem Approach (EAFM) in the Bengkalis Strait, Bengkalis Regency, Riau Province - Adiwanarta, Rizki; Adriman, Adriman; Efizon, Deni (Faculty of Fisheries and Marine, Universitas Riau, 2023)
Fish resources are one of the natural resources that must be used as much as possible for the welfare of the community, especially around Riau Province, where part of its territory is a coastal area that has a wealth of marine biological resources that have the potential to be developed at present and in the future. One type of marine biological resource that has high economic value is the most abundant fish resource. The methods used in this study are the direct observation survey method, interviews, and distributing questionnaires. The data used in this research consists of primary and secondary data. Primary data is obtained from the results of observations and measurements made in the field, including interviews with respondents, while secondary data is in the form of excerpts from previous research journals and activity report documents obtained from related institutions or agencies. grouping based on composite value, i.e., domains that qualify as